2009
DOI: 10.1038/nrneph.2009.213
|View full text |Cite
|
Sign up to set email alerts
|

Fluid balance and acute kidney injury

Abstract: Intravenous fluids are widely administered to patients who have, or are at risk of, acute kidney injury (AKI). However, deleterious consequences of overzealous fluid therapy are increasingly being recognized. Salt and water overload can predispose to organ dysfunction, impaired wound healing and nosocomial infection, particularly in patients with AKI, in whom fluid challenges are frequent and excretion is impaired. In this Review article, we discuss how interstitial edema can further delay renal recovery and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
270
3
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 409 publications
(304 citation statements)
references
References 111 publications
9
270
3
12
Order By: Relevance
“…81 Fluid overload results in tissue edema; in an encapsulated organ such as the kidney, tissue edema may participate directly in the progression of AKI as the kidney lacks the capacity to accommodate additional volume without an increase in interstitial pressure and compromised organ blood flow. 82 Within an ERAS protocol, postoperative hypotension and low UOP are common within the first 24 hr, whereas renal dysfunction is extremely rare. 83 Therefore, in the absence of other concerns, detrimental postoperative fluid overload is not justified, and ''permissive oliguria'' can be tolerated.…”
Section: Low Perioperative Uopmentioning
confidence: 99%
“…81 Fluid overload results in tissue edema; in an encapsulated organ such as the kidney, tissue edema may participate directly in the progression of AKI as the kidney lacks the capacity to accommodate additional volume without an increase in interstitial pressure and compromised organ blood flow. 82 Within an ERAS protocol, postoperative hypotension and low UOP are common within the first 24 hr, whereas renal dysfunction is extremely rare. 83 Therefore, in the absence of other concerns, detrimental postoperative fluid overload is not justified, and ''permissive oliguria'' can be tolerated.…”
Section: Low Perioperative Uopmentioning
confidence: 99%
“…Clinically this fluid overload is apparent as peripheral and pulmonary oedema, although other organs may be affected [1]. A number of cohort studies have demonstrated an association between fluid overload and mortality [2][3][4], and it has been suggested that strategies aimed at prevention or treatment of fluid overload may be beneficial following haemodynamic stabilisation [5].…”
Section: Introductionmentioning
confidence: 99%
“…In patients treated for sepsis, the combination of increased capillary permeability and increased intravascular hydrostatic pressure from fl uid loading both favor the accumulation of extracellular fl uid. Tissue edema is not a benign condition, as it can result in impaired tissue oxygenation, obstruction of capillary blood fl ow, disruption in metabolite clearance, and altered cell-cell interactions (15).…”
Section: Discussionmentioning
confidence: 99%